2019
DOI: 10.3390/buildings9070167
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Best 3D Viewpoint within the BIM Model: Application to Visual Tasks Related to Facility Management

Abstract: Visualizing building assets within building information modeling (BIM) offers significant opportunities in facility management as it can assist the maintenance and the safety of buildings. Nevertheless, taking decisions based on 3D visualization remains a challenge since the high density of spatial information inside the 3D model requires suitable visualization techniques to achieve the visual task. The occlusion is ubiquitous and, whilst solutions already exist such as transparency, none currently solve this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…This statement has been demonstrated (at the confidence level of 95%) both for the accuracy and user's certainty criteria. With the work of (Neuville et al, 2019a), this study brings thus further empirical evidence that supports the viewpoint value in achieving visual purposes. Once again, it points out that current default software points of view (despite their suitability in 3D modeling) show limitations in visualizing 3D geospatial data, especially when visualization is used for spatial analysis.…”
Section: Back To the Research Questionssupporting
confidence: 52%
See 2 more Smart Citations
“…This statement has been demonstrated (at the confidence level of 95%) both for the accuracy and user's certainty criteria. With the work of (Neuville et al, 2019a), this study brings thus further empirical evidence that supports the viewpoint value in achieving visual purposes. Once again, it points out that current default software points of view (despite their suitability in 3D modeling) show limitations in visualizing 3D geospatial data, especially when visualization is used for spatial analysis.…”
Section: Back To the Research Questionssupporting
confidence: 52%
“…In this context, Rautenbach et al, (2015) indicates that the camera location may have a great impact on the visual selectivity purpose. This is also the conclusion of (Neuville et al, 2019a) who showed that a 3D viewpoint that maximizes 3D geometric objects' view area within the viewport significantly improves visual counting accuracy and user's certainty (compared to default software points of view). Although this study brings initial empirical evidence that supports the viewpoint usability in 3D geovisualization, it only considers visual counting (selectivity task).…”
Section: Research Questionsmentioning
confidence: 52%
See 1 more Smart Citation
“…Managing data challenges in operation and maintenance (O&M) process of structures promote researchers to use BIM in facility management (FM) and combine it with other methods such as Data Mining (DM) to extract useful patterns and data, Performance Information Model (PIM) to obtain an integrated model, Thermal Infrared Sensing (TIS) to prepare a complete as-built BIM, a System Information Model (SIM) for asset management, IoT for helping decision making in facilities management, Quick Response (QR) codes or image algorithms for integration of facility information and repair process, and laser scanning or Radio Frequency Identification (RFID) for indoor localization of facilities [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. For increasing the visualization quality in FM, the performance of a RESTful web application based on a BIM model was examined by researchers to show its benefits than traditional points of view [ 74 ]. Moreover, the efficiency of integration of the BIM technologies with real-time remote sensing tools on FM process was examined to show the progress of indoor maintenance monitoring and decision making during building life-cycle management [ 75 ].…”
Section: Content Analysismentioning
confidence: 99%
“…Whilst many researchers have pointed out the usefulness of 3D cadastre visualization in combination with the BIM, Neuville et al (2019) state that decision-making based on 3D visualization remains a challenge due to the high density of spatial information inside the 3D model. To alleviate the ubiquitous risk of occlusion, the authors suggested algorithms for automatic 3D viewpoint management that optimize visibility of objects inside the viewport.…”
Section: Related Workmentioning
confidence: 99%